ASSA14-03-04 Circulating hematopoietic progenitor cells in patients undergoing coronary artery bypass graft surgery. (1st December 2014) - Zhang, L; Wang, R; Xiao, C; Wu, Y; Gao, C
Abstract : Objective: To evaluate the change of circulating hematopoietic progenitor cells (cHPCs) in patients undergoing coronary artery bypass graft surgery. Methods: 51 patients who were scheduled to undergo elective coronary artery bypass graft surgery were prospectively enrolled in this study. Blood samples were collected at baseline, on postoperative day 1, postoperative day 3 and postoperative day 5. The CD34 + CD45dim, CD133 + CD45dim, CD34 + CD133 + CD45dim cell were measured by flow cytometry. Circulating progenitor cell functions were studied in vitro by clonogenic and migration assays. Results: All elective patients showed a significant post-operative increase of CD34 + CD45dim (1.51 ± 1.26 vs 2.02 ± 1.16, p = 0.036) and CD133 + CD45dim cells (1.16 ± 0.85 vs 1.65 ± 0.99, p = 0.008), irrespective of on-pump CABG or off-pump CABG. The periopoerative change of cHPCs level in patients undergoing on-pump surgery was more significant than that in patients with off-pump surgery. Conclusion: Patients undergoing elective cardiac surgery demonstrated an increase in cHPC level postoperaively.